1996
DOI: 10.1126/science.274.5284.114
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activation Modulated by Sentence Comprehension

Abstract: The comprehension of visually presented sentences produces brain activation that increases with the linguistic complexity of the sentence. The volume of neural tissue activated (number of voxels) during sentence comprehension was measured with echo-planar functional magnetic resonance imaging. The modulation of the volume of activation by sentence complexity was observed in a network of four areas: the classical left-hemisphere language areas (the left laterosuperior temporal cortex, or Wernicke's area, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

93
705
9
11

Year Published

1999
1999
2003
2003

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 982 publications
(818 citation statements)
references
References 24 publications
93
705
9
11
Order By: Relevance
“…Broca's area was shown to be involved in syntactic processes in a number of neuropsychological studies, in particular in that patients with lesions including Broca's area clearly suffering from syntactic deficits (Grodzinski, 2000;Caplan and Waters, 1999). In addition, some recent brain imaging studies have demonstrated increased hemodynamic activity in Broca's area during the processing of syntactic aspects during language comprehension (Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2000a;Just et al, 1996;Moro et al, 2001;Tettamanti et al, 2002). Some of these fMRI studies report the activation to be focused in BA44.…”
Section: Discussionmentioning
confidence: 99%
“…Broca's area was shown to be involved in syntactic processes in a number of neuropsychological studies, in particular in that patients with lesions including Broca's area clearly suffering from syntactic deficits (Grodzinski, 2000;Caplan and Waters, 1999). In addition, some recent brain imaging studies have demonstrated increased hemodynamic activity in Broca's area during the processing of syntactic aspects during language comprehension (Dapretto and Bookheimer, 1999;Embick et al, 2000;Friederici et al, 2000a;Just et al, 1996;Moro et al, 2001;Tettamanti et al, 2002). Some of these fMRI studies report the activation to be focused in BA44.…”
Section: Discussionmentioning
confidence: 99%
“…As cognition become more intensive or demanding, attention is called to help drive the computational machinery. For example in a functional MRI study of sentence comprehension, Just et al (1996) demonstrated that the increasing linguistic complexity of sentences produced a proportionate increase of activation of the classical left hemisphere language system in healthy controls. By the same token, processes that are presumed automatic and involuntary may also be effected, with attention disregulation perhaps leading to states of hyper-automaticity (Callaway and Naghdi, 1982).…”
Section: Neuroscience Of Attentionmentioning
confidence: 99%
“…These findings were generexamined through lesion studies and recently with the use ally replicated in another study by the same group with of functional neuroimaging. Evidence from these studies auditory presentation in which subjects judged the suggests that syntactic processes are supported, at least in plausibility of cleft-subject and more complex cleft-object part, by the left inferior frontal gyrus, or Broca's area sentences, except that the activation was in pars trian-[7-10, 13,17,19,22,23,41]. (Note that the posterior left gularis rather than pars opercularis [8].…”
Section: Introductionmentioning
confidence: 99%
“…[8, 13,17,19,23,41]. For example, in one of the studies mentioned above [39], patients with lesions confined to the frontal operculum and extending posteriorly had significant 2 .…”
Section: Introductionmentioning
confidence: 99%